(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, "History of Bukhara" written by Bukhara historian scholar Abu Bakr Muhammad ibn An Narshahi, who has a special place among the sources of information about the 8th-12th centuries of the Middle Ages and provides valuable information about the socio-economic, political and spiritual life of Movarunnahr and Khorasan. In his work, information related to the history of Bukhara is presented.